Plan de negocios, mediante el estudio de mercado, para proponer la creación del centro gastronómico étnico cultural "Mikuna Kallari" en la parroquia Lumbaqui del cantón Gonzalo Pizarro - Guzmán Guzmán, Lorena Maribel (2016)
This research to make a business plan by the Market to propose the creation of ethnic culinary cultural center "Mikuna Kallari" Lumbaqui parish in Canton Gonzalo Pizarro for the purpose of meeting the current unmet demand for food services offered in the field of study thereby strengthen the food tourism by creating the same, providing a unique and varied service. In the process of the investigation a situational diagnosis of the study area which explains characteristics of the physical environment, population of the corner, socio-economic analysis, housing and basic services, socio-cultural system and cultural diversity was held, also an analysis was conducted Market surveys applying a model aimed at tourists and residents in order to know the opinion of the existing gastronomy in the canton and to be able to project, the results obtained indicates that 87% of respondents confirm your creation of gastronomic center, technical study on the project size, location, distribution and engineering of the project discussed in the latter the respective process diagrams regarding service and preparation of a dish and distribution of the plant through a plane is designed; various financial parameters was performed as income - Expenses, VAN, TIR, Cost / Benefit, recovery period allowing them to study the legal steps for the establishment and implementation of the gastronomic center of the economic study was investigated determines that it is entirely feasible the creation of ethnic culinary cultural center in Lumbaqui Mikuna Kallari parish. To carry out the research corresponds to a non-experimental design is based on the documentary and descriptive field research, using techniques such as observation and surveys.